Evaluation of Pollution of Mining Areas in Aspect of their Future Use and Development - J. Kudelko; D. J. Pyra; Korzekwam W. (Society for Mining, Metallurgy & Exploration, 2005)
Polkowice region (Lower Silesia, Poland) is an area, where the copper mining activity started about 40 years ago and new technologies were applied. There are 3 underground mines, 3 processing plants, tailings pond (the biggest one in Europe), pipelines for flotation waste transport, railways. Although new technologies were applied during the copper ore exploitation, the environment in this area were polluted mostly by dust containing copper, lead, zinc and arsenic. Estimated values of heavy metals in polluted soils were compared to the natural contents of this metals. The geochemical background for Polkowice area was defined. The pollution zones occur around mining facilities. Copper ore exploitation and processing is planned for the next 20-40 years depending on market situation. After mines and other facilities closing the most important problem will be sustainable development of this area. To evaluate the scope of revitalization activities the analysis of recent soil environment condition will be necessary as well as forecasts for pollution migration. Geostatistic methods used also in mining will be very helpful for this task.